Cimentos endodônticos à base de silicato de cálcio: avaliação in vitro de diferentes parâmetros de interesse - Domingos, Camila Maria Peres de Rosatto (2021)
Since the appearance of the first calcium silicate-based sealer, several others sealers have been launched on the market, some in powder and liquid form and others ready-for-use. It is not yet known how is the performance of this material in different cell types found in the periapical region and the difficulties that may be discovered during the cleaning of the dentinal walls in post space for fiber post cementation. Or even if may occur changes in the composition of the sealers and their properties, due to the use of irrigating solutions to remove the remaining residues of these sealers. Therefore, the present study involved five specific in vitro objectives. Objective 1: to evaluate the cytotoxicity and cytokine release after exposure of monocytes and polymorphonuclears cells obtained from the peripheral blood of humans to different fresh root canal sealers (Sealer 26, AH Plus and EndoSequence BC Sealer). Apoptosis and necrosis was assessed by flow cytometry and cytokine measurement (IL-4, IL-6, IL-8, IL-10, IL-12) by ELISA. It was demonstrated that the effect of toxic agents released varied depending on the cell type and that the composition of the sealers appeared to alter the form of self-regulation in the production of these cytokines by cells. Objective 2: to evaluate the physicochemical and biological properties of ready-to-use calcium silicate-based sealers (EndoSequence BC Sealer [END], Bio-C Sealer [BC] and Sealer Plus BC [SPBC]), using osteoclast primary culture. The cytotoxicity was assessed using the MTT test and the inhibition of osteoclastogenesis by TRAP. The solubility of the sealers was tested by calculating the mass loss in culture medium and deionized water. The pH of the solutions was measured, as well as the presence of calcium and silicon ions by X-ray fluorescence spectroscopy (XRF). END showed greater cell viability compared to other sealers and BC showed greater inhibition of osteoclasts. All sealers showed high solubility, greater than that recommended by the standards of the International Organization for Standardization (ISO). The presence of silicon ions was extremely low for all sealers. Objective 3: to evaluate the cytotoxicity, cell adhesion and chemical characteristics of calcium silicate-based sealers (BioRoot RCS [BR], Bio-C Sealer [BC] and Sealer Plus BC [SPBC]), using RAW264.7 cells. The cytotoxicity was assessed by MTT test and sealer discs were used to evaluate cell adhesion, beyond to chemical characterization with XRF, scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX). The composition of unset sealers and after setting was also evaluated by Fourier-transform infrared spectroscopy (FTIR). SPBC revealed the lowest cell viability compared to the other sealers. Comparing the experimental groups with the control group, the 1: 1 dilution showed a reduction significant in viability for all materials. BC and SPBC presented similar spectra in FTIR. EDX demonstrated a greater presence of calcium for BR and SPBC, with the presence of aluminum in ready-to-use sealers. XRF also showed an amount of calcium significantly higher for BR compared to other sealers. Precipitates were found on the surface of all materials. BR showed the greatest degree of purity and the highest calcium content, while BC and SPBC presented similar compositions. All the sealers maintained viability above 70%. Objective 4: to evaluate whether solutions (NaOCl and NaOCl+EDTA) and their activations (manual, passive ultrasonic irrigation and Easy Clean tip) are able to promote the cleaning of the dentinal walls after post space preparation, where MTA Fillapex sealer was used, by microcomputed tomography (micro-CT); and whether these cleaning protocols are capable to change the dentin microhardness, assessed by Knoop indentation. This objective showed that the Easy Clean tip removed more debris inside the root canal after post space and that the cervical third presented the greatest cleanliness. In addition, the NaOCl+EDTA solution was more effective in cleaning, regardless of the activation method. No cleaning protocol was able to modify the dentin microhardness. Objective 5: to evaluate whether cleaning protocols using solutions (NaOCl and NaOCl+EDTA) and passive ultrasonic irrigation, change the composition of calcium silicate-based sealers (EndoSequence BC Sealer, BioRoot RCS and Bio-C Sealer) fresh and after setting in a post space root canal, using a device that was created for the simulation. The composition of the sealers after the cleaning protocols was evaluated using Raman and EDX spectroscopy. It was observed that regardless of the protocols, the cleaning of the remnants in a post space root canal for installing a fiberglass post should be recommended only after setting of the bioceramic sealer. It can be concluded from the presented objectives, the new calcium silicate-based endodontic sealers showed adequate physico-chemical properties, except for solubility. Regarding the biological properties, behave in different ways in face of different cell types present in the periapical region. In addition, in the face of need for rehabilitation with a fiberglass post posteriorly the filling with this type of material, the cleaning protocols used showed effectiveness, without causing changes in the composition of calcium silicate-based sealers and that the Easy Clean tip promotes better cleaning of the remnants adhered to the dentinal walls.